The Criterion Validity, Reliability, and Feasibility of an Instrument for Assessing the Nursing Intensity in Perioperative Settings - Satu Rauta; Sanna Salanterä; Tero Vahlberg; Kristiina Junttila (Nursing Research and Practice)
Patient classification systems generate information for staff allocation based on a patient’s care needs. This study aims to test further the instrument for assessing nursing intensity (NI) in perioperative settings. Nine operating departments from five university hospitals were involved. The perioperative nurses gathered data from patients (N=876) representing different fields of surgery. Reliability was tested by parallel classifications (n=144). Also, the users’ (n=40) opinions were surveyed. The results support the predictive validity and interrater reliability of the instrument. The nurses considered the instrument feasible to use. The patients’ low ASA class did not automatically signify low NI; however, high ASA class was more frequently associated with high intraoperative NI. Intraoperative NI indicated the length of the postanaesthesia care and the type of the follow-up unit. Parallel classifications ensured the homogenous use of the instrument. The use of the instrument is recommended.